2022
DOI: 10.1007/s12026-022-09287-8
|View full text |Cite
|
Sign up to set email alerts
|

Association of hepatitis B vaccine response to vitamin D supplementation and ultraviolet B (UVB) exposure during different time intervals in experimental animals

Abstract: The implications of vitamin D deficiency on the immune system have become clearer in recent years, being associated with less immune response following HBV vaccine. We aimed to elucidate the effect of vitamin D supplementation and UVB exposure on short- and long-term performance of hepatitis B vaccine. Forty-five male rabbits were randomly divided into 3 groups that were immunized with recombinant HBsAg. The first group (group I) represented a negative control group, whereas group III rabbits were administered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Adequate vitamin D levels are closely related to the development of effective vaccine responses against HBV. The influence of vitamin D supplementation on the course of short- and long-term HBV vaccination was investigated in a recent study [ 69 ]. This showed that vitamin D levels were positively associated with anti-HBsAg IgG levels and the percent avidity in patients receiving vitamin D supplementation [ 69 ].…”
Section: Possible Mechanisms Of the Association Between Vitamin D–vdr...mentioning
confidence: 99%
See 1 more Smart Citation
“…Adequate vitamin D levels are closely related to the development of effective vaccine responses against HBV. The influence of vitamin D supplementation on the course of short- and long-term HBV vaccination was investigated in a recent study [ 69 ]. This showed that vitamin D levels were positively associated with anti-HBsAg IgG levels and the percent avidity in patients receiving vitamin D supplementation [ 69 ].…”
Section: Possible Mechanisms Of the Association Between Vitamin D–vdr...mentioning
confidence: 99%
“…The influence of vitamin D supplementation on the course of short- and long-term HBV vaccination was investigated in a recent study [ 69 ]. This showed that vitamin D levels were positively associated with anti-HBsAg IgG levels and the percent avidity in patients receiving vitamin D supplementation [ 69 ]. In contrast, another study examining the effect of oral vitamin D 3 supplementation on HBV vaccination showed that vitamin D supplementation starting 3 days after vaccination had no effect on the vaccination response [ 70 ].…”
Section: Possible Mechanisms Of the Association Between Vitamin D–vdr...mentioning
confidence: 99%
“…One study suggests that vitamin D status might play a role in the persistence of anti-HBs antibodies and the durability of protection following primary vaccination with a recombinant HB vaccine. 12,14 Conversely, another study reveals a significant and inverse correlation between vitamin D levels and HBV-DNA. 14,15 However, a separate study contends that vitamin D status has no bearing on the anti-HBs titer in children who received hepatitis B virus vaccination during infancy.…”
Section: Introductionmentioning
confidence: 97%
“…12,14 Conversely, another study reveals a significant and inverse correlation between vitamin D levels and HBV-DNA. 14,15 However, a separate study contends that vitamin D status has no bearing on the anti-HBs titer in children who received hepatitis B virus vaccination during infancy. 16 Some studies even report a lack of connection between vitamin D levels and HBV viral infection.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation